Type 1 diabetes mellitus in children and adolescents of Russian Federation: key epidemiology trends - Tatiana Yur'evna Shiryaeva; Ekaterina Andreevna Andrianova; Yury Ivanovich Suntsov (Сахарный диабет)
Aims. To evaluate key epidemiology trends for type 1 diabetes mellitus (T1DM) in children and adolescents of Russian Federation during 2001?2011 yy. Materials and Methods. Dynamics of incidence, prevalence and mortality from T1DM were assessed for national population and, separately, for all federal regions over the 2001?2011 yy. based on the questionnaires developed in the Institute of Paediatric Endocrinology (Endocrinology Research Centre) and data from the State Register of Diabetes Mellitus. Results. 18,392 children aged 0 to 14 years and 8934 adolescents with T1DM were registered in Russian Federation by 01.01.2012. T1DM incidence in 2011 was estimated at 2407 among children and 1276 among adolescents. Mean T1DM prevalence across the Federation reached 72.8, incidence 12.43 (3.39?14.06) and mortality 0.07 (0.0?0.26) per 100,000 of relevant population (r.p.). Incidence rate for 2001?2011 indicates a 30% increase for past 11 years with average annual increase of 2.82%. According to the prognosis developed from these data, in 5 years T1DM incidence among children will reach 13.61 per 100,000 of r.p. Highest incidence was registered in Ural Federal Region (17.43 per 100,000 of r.p.) that assumed this position from North-Western federal region with 15.42 per 100,000 of r.p. as of 01.01.2010). T1DM incidence in adolescents is estimated at 15.26 per 100,000 r.p. with prevalence of 92.6 per 100,000 r.p. Incidence rate increased by 10.5% during past 6 years with average annual increase of 0.97%. Conclusion. This survey indicates that key epidemiological trends for T1DM in children and adolescents of Russian Federation correspond to average world parameters.